Safety of Antiplatelet Therapy in Noncardioembolic Ischemic Stroke With Thrombocytopenia: The CASE II Study - Dongjuan Xu; Huan Zhou; Tingxia Zhang; Weiwei Gong; Jieming Zhong; Han Yu; Fujian Chen; Wansi Zhong; Shenqiang Yan; Min Lou (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background There is scant evidence regarding the safety of antiplatelet therapy in acute ischemic stroke (AIS) patients with thrombocytopenia. Our study aims to address this concern by examining AIS patients with thrombocytopenia from a large database in real‐world settings. Methods and Results We included patients with AIS with a platelet count <100×109/L who had complete records of antiplatelet drug use. Those requiring anticoagulation or having contraindications to antiplatelet therapy were excluded. Short‐term safety outcomes were in‐hospital bleeding events, while the long‐term safety outcome was 1‐year all‐cause mortality. A good clinical outcome was defined as functional independence, indicated by a modified Rankin Scale score of 0 to 2 at discharge. Propensity score matched analyses were used. We screened 169 423 patients with AIS from 90 stroke centers in the CASE II register, ultimately enrolling 2808 noncardioembolic patients with thrombocytopenia. In the propensity score matched analyses, no significant difference was observed between the antiplatelet and nonantiplatelet groups in terms of intracranial hemorrhage (odds ratio=0.855 [95% CI, 0.284–5.478]; P=0.160) or gastrointestinal bleeding (odds ratio=2.034 [95% CI, 0.755–5.478]; P=0.160). Antiplatelet therapy was associated with improved functional outcomes at discharge (odds ratio=1.405 [95% CI, 1.028–1.920]; P=0.033), and showed a trend towards reducing 1‐year mortality (odds ratio=0.395 [95% CI, 0.152–1.031]; P=0.058). Conclusions The use of antiplatelet therapy lessened as platelet count decreased in patients with AIS with thrombocytopenia. However, our findings suggest that antiplatelet medications remain safe and effective for this population.